ANALYSIS OF THE DETERMINANTS OF DIVIDEND PAYOUT OF CONSUMER GOODS FIRMS IN NIGERIA - OKORO, Cyprian Okey; EZEABASILI, Vincent; ALAJEKWU, Udoka Bernard (Annals of Spiru Haret University. Economic Series, 2018)
The study examines determinants of dividend payout of consumer goods firms listed on the Nigerian Stock Exchange. The Nigerian Stock Exchange has 28 listed consumer goods firms. Purposive sampling technique was used and a sample of 9 consumer goods firms for duration of ten years from 2006 to 2015 was selected. Secondary data was collected from audited financial statements of the companies from the websites of the selected firms. Dividend payout ratio was the dependent variable while independent variables were market value, profitability, financial leverage, firm size and previous year dividend payout. Descriptive statistics and multiple regressions were used. Results showed that firm market value has significant positive effect on dividend payout; firm profitability has positive but insignificant effect on dividend payout; firm leverage has negative and insignificant effect on dividend payout; firm size has negative and insignificant effect on dividend payout; and previous year’s dividend has significant positive effect on dividend payout. The study thus concluded that market value and previous year’s dividend are the major determinants of dividend payout in consumer goods sector in Nigeria.